Integrated aquaculture: a tool for sustainable development/food security and poverty alleviation in achieving MDG’s goals (2014)
Aquaculture is a multiculture of plants and animals in an aquatic environment. Thereby aquaculture is enriched through integration of formerly existing cultivation of crops cum horticultural, and /or agronomical or domesticated animals such as piggery, poultry, rabbitery or even wild domesticated animals such as guinea fowls, and cane rats. Hence, this study investigated integrated aquaculture cum horticulture as a possible tool for sustainable food production in order to ensure food security in Nigeria and alleviate poverty. The study utilized four homestead concrete tanks located at the back of my house in University of Ibadan senior staff quarters. Catfish bloodstock’s males and females were used to raise fry through fingerlings to juveniles to adult fish. Data were taken at each stage of the fish life cycle i.e. the products harvested and sales. Data on numbers of horticultural trees planted were taken and numbers of produce at harvest were recorded. These data were collated and analyzed yearly and at the end of the 10- year period. The result showed that diversification in integrated aquaculture ensures better environmental and on farm resource management which is much needed globally but much more in the developing countries for food security and poverty alleviation. At each point in time, there is one product or the other available for consumption or for sale which ensured better cash flow. During the dry season the drought was ameliorated by the availability of water for wetting the crops and incorporation of vegetables growing into the system. Horticulture cum fish farming integrated system has been adjudged recently to be a solution to drought, poor soil condition management; climate change along with unsustainable water management and farming practices. This study showed that this system is more natural and sustains better food production practice. It is capable of bringing food production closer to urban consumers who do not have access for extensive farm land and reduces the transport cost in retail food marketing.